Rasbora borneensis fish and Vigna unguiculata legume protein supplementation restores reproductive hormone profiles in early-life protein-deficient female rats - Didik Dwi Sanyoto; Triawanti; Sherly Limantara; Juhairana; Nani Zaitun; Haitami; Dimas Ikhsan Airlangga; Metria Zeta; Muhammad Athaya Zein (Indonesian Society for Biochemistry and Molecular Biology, 2026)
Background: Protein malnutrition during early development can alter the hormonal pathways essential for female reproductive maturation. It remains a significant concern in regions where inadequate protein intake contributes to stunting and long-term reproductive risks. However, evidence remains limited regarding how maternal and early-life protein deficiency affects reproductive hormone formation in offspring, and whether locally available nutrient sources can reverse these disruptions. Objective: This study evaluated the effects of supplementation of Rasbora borneensis and Vigna unguiculata spp. cylindrica on reproductive hormones in female rat offspring subjected to protein deficiency. Methods: A protein-deficient model was generated by feeding rats a low-protein AIN-76A diet from birth to weaning, followed by continuation of the same diet in female offspring for four weeks. The offspring were then assigned to a normal control group receiving a standard diet, a negative control group maintained on the low-protein diet, and three treatment groups receiving Seluang fish feed, cowpea cowpea feed, or a combination of both for four weeks. FSH and estrogen levels were assessed to evaluate reproductive endocrine function. Results: All treatment diets increased FSH and estrogen levels compared with the negative control. FSH concentrations were significantly higher in all treatment groups (p = 0.012), with the combination diet yielding the greatest increase. Estrogen levels also rose substantially in the treatment groups with statistical analyses confirming significant differences (p < 0.001). Conclusion: Seluang fish and Nagara cowpea effectively improved reproductive hormone profiles in protein-deficient female rats, highlighting their potential as relevant nutritional strategies to counter early-life protein malnutrition.